To be diurnal or nocturnal: the interplay of energy balance and time of activity in subterranean rodents (Ctenomys aff. knighti) and laboratory mice (Mus musculus) - Silva, Patrícia Tachinardi Andrade (2017)
Studies that show discrepancy between nocturnal and diurnal activity under laboratory and field conditions, respectively, have become increasingly common in rodents and suggest that the definition of temporal niche is far more plastic than originally suspected. Recently, it has been proposed that factors that challenge the animal\'s energy balance play an important role in temporal niche switches. Food availability and environmental temperatures could then be one of the fundamental differences between field and laboratory that could alter the temporal daily pattern of activity. In laboratory, animals are fed ad libitum, while in nature they need to expend energy for foraging. The \"circadian thermo-energetics hypothesis\" suggests that daytime activity could be a response to the high energetic costs of foraging, allowing the animal to save energy during the cooler night hours by resting and taking shelter in burrows where temperatures are higher than on the surface. In this thesis, we explored the interplay of plasticity in nocturnal/diurnal activity definition and energetic metabolism in two rodent species, tuco-tucos (Ctenomys aff. knighti) and laboratory mice (Mus musculus). Tuco-tucos are subterranean rodents which face peculiar energetic challenges in their habitat and were shown to be diurnal in the field and nocturnal in the laboratory. We characterized how their energy expenditure varies across day and night and described the peculiar finding of some factor inside the metabolic chamber being itself a trigger for the nocturnal to diurnal switch. Moreover, we estimated the amount of energy tuco-tucos would save by being diurnal in the field, by combining metabolic rate measurements at various ambient temperatures with records of environmental temperature in the tuco-tuco\'s natural habitat. We also described further investigations of circadian plasticity in both locomotor activity and body temperature of laboratory mice subjected to food restriction in semi-natural conditions. The findings of these three studies provided valuable evidence for the discussion of the role of environmental factors, particularly energetic challenges, in the plasticity of daily rhythms